Linear polarization of photons produced by the electrons moving along the crystallographic plane in a silicon crystal - Denyak, V.V.; Khvastunov, V.M.; Likhachev, V.P.; Paschuk, S.A.; Schelin, H.R. (Вопросы атомной науки и техники, 2001)
We present the results of the polarization and intensity measurements versus photon energy Eg=5-35 MeV for the photon beam produced by the electrons with the energies 1.2 and 1.5 GeV moving in the silicon crystal 500 and 290 mm thick along the (110) plane. The comparison with results of another research group and theoretical calculation indicates the qualitative agreement. The correlation in the shape of the radiation intensity spectrum and its polarization energy dependence is observed.